Primary Cutaneous Spindle Cell B-Cell Lymphoma of Follicle Origin Mimicking Acne Rosacea. (June 2015) - Garrido, María C.; Rios, Juan J.; Riveiro-Falkenbach, Erica; Escamez, Pilar J.; Ronco, Maria A.; Rodríguez-Peralto, Jose L.
Abstract : Abstract: Primary cutaneous spindle cell lymphoma is a unique morphologic variant of cutaneous B-cell follicle center lymphoma characterized by a prominent population of spindle-shaped, medium, and large B lymphocytes with a poorly formed storiform pattern. We report a case of a 35-year-old woman who presented with a well-defined erythematous plaque with 2 nodular, nontender nonscaling nonulcerated lesions on her right cheek mimicking acne rosacea. Microscopic examination revealed a tumor mainly centered in the reticular dermis and mostly composed of spindle-shaped large B lymphocytes exhibiting bizarre shapes with "boomerang-like" or "spermatozoa-like" appearance. The immunohistochemical staining demonstrated neoplastic lymphocytes positive for CD20, CD79α, and BCL-6, and negative for CD3, CD43, CD10, BCL-2, and MUM-1. These results supported the diagnosis of a follicle center B-cell lymphoma with spindle cells. Although this rare variant of primary cutaneous B-cell lymphoma is not included in the recent WHO–EORTC classification, the rarity of this tumor and its unique morphologic appearance frequently leads to misdiagnosis and delays its treatment.